CHARACTERISTICS OF PERIPHERAL BLOOD CELL INDICES IN PATIENTS WITH DIABETES AT THE NATIONAL HOSPITAL OF ENDOCRINOLOGY IN 2023 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe abnormalities in selected peripheral blood cell indices of red blood cell, white blood cell, and platelet lineages among inpatients with diabetes mellitus at the National Hospital of Endocrinology in 2023. Subjects and methods: A cross-sectional descriptive study was conducted on 306 inpatients with diabetes mellitus treated at the Department of Diabetes, National Hospital of Endocrinology, from March to August 2023. Peripheral blood cell indices were classified as decreased, normal, or increased according to the reference ranges used in the study. Results: Patients aged 45 years and older accounted for 84,0%, with a mean age of 59,87 ± 13,86 years. Regarding red blood cell parameters, decreased HCT, HGB, and RBC were observed in 35,0%, 25,8%, and 23,9% of patients, respectively; RDW-CV >14% was found in 34,3%. For white blood cell parameters, increased WBC, NEUT, and MONO were observed in 18,6%, 20,9%, and 69,9% of patients, respectively. Most patients had platelet counts within the normal range, while increased MPV and decreased PDW were recorded in 55,2% and 23,9% of patients, respectively. Conclusion: Inpatients with diabetes mellitus showed several changes across all three peripheral blood cell lineages, notably decreased HGB and HCT, and increased RDW-CV, MONO, NEUT, and MPV. Complete blood count testing may provide additional supportive information for monitoring anemia-related findings, white blood cell changes, and platelet indices in patients with diabetes mellitus.
Keywords: hematology, peripheral blood cells, diabetes mellitus